RELATIONSHIP OF STUDENT'S PERCEPTION ON TEACHER'S PERCEPTION AND PERFORMANCE WITH THE STUDENTS JURISPRUDENCE LEARNING RESULTS OF MTS AL-WASHLIYAH POOL, PERCUT SEI TUAN DISTRICT - Ritonga, Asnil Aidah; Salamuddin, Salamuddin; Hasibuan, Ilhamuddin (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2021)
This study aims to determine: (1) The relationship between students' perceptionsof pedagogical competence and student fiqh learning outcomes, (2) Therelationship between teacher performance and student fiqh learning outcomes,(3) The relationship between students' perceptions of pedagogical competenceand teacher performance with student learning outcomes. learn fiqh students.This type of quantitative research with correlation research methods. Thepopulation is 107 students with a sample of 36 students taken by randomsampling technique. The data collection technique used is a non-test technique.The non-test technique, namely a questionnaire, was used to collect data onstudent perceptions of pedagogical competence and teacher performancevariables. While the variable of student fiqh learning outcomes through theresults of learning evaluation. The data analysis technique used is correlationand regression. The research results show: (1) there is a positive and significantcontribution between competencies pedagogy with student learning outcomesMTs. Al-Washliyah Percut Sei Tuan, (2) there is a positive and significantcontribution between teacher performance with student learning outcomes MTs.Al-Washliyah Percut Sei Tuan, and (3) there is a positive and significantcontribution together between pedagogical competence and teacher performanceÂ with learning outcomes students of MTs. Al-Washliyah Percut SeiT uan.